Exploring Factors That Facilitate Acculturation Strategies and Academic Success of West African Immigrant Youth in Urban Schools. Issue 1 (January 2020) - Kumi-Yeboah, Alex; Brobbey, Gordon; Smith, Patriann
Immigrant students in U.S. educational system experience challenges learning to adapt and integrate into new educational environments. Little is known, however, about factors that facilitate acculturation strategies of immigrant youth from West Africa and how they affect their academic success and challenges faced. Considering the current political discourse over the influence of immigration in U.S. schools, 20 immigrant youth from Ghana and Nigeria were recruited and interviewed in the metropolitan area of New York City. Analyses of semi-structured interviews revealed that teacher, parent, and peer support; social and electronic media; and extracurricular activities emerged as the factors that helped acculturation strategies and academic success. Challenging factors were dealing with sociocultural differences; discrimination, stress, and social integration; and language differences. The article discusses the implications of these findings for teachers to understand acculturation strategies to help West African immigrant youth to adapt, acculturate, and integrate into new school environments.